Gulf of Mexico Hypoxia: Land and Sea Interactions - Downing, John A.; Baker, James L.; Diaz, Robert J.; Prato, Tony; Rabalais, Nancy N.; Zimmerman, Roger J. (Council for Agricultural Science and Technology (CAST), 1999)
A CAST task force of 6 scientists provides recommendations to help better understand all aspects of hypoxia in the Gulf of Mexico and other areas of the world, and to decrease the Gulf hypoxic zone.
Keywords: Mexico Hypoxia; Sea Interactions; Gulf Hypoxic Zone